Changes in maxillofacial morphology and velopharyngeal function with two-stage maxillary distraction–mandibular setback surgery in patients with cleft lip and palate. Issue 3 (March 2018) - Susami, T.; Mori, Y.; Ohkubo, K.; Takahashi, M.; Hirano, Y.; Saijo, H.; Takato, T.
Abstract: Maxillary distraction is increasingly used for the correction of severe maxillary retrusion in patients with cleft lip and palate. However, control of the maxillary movement is difficult, and the need to wear visible distractors for a long period of time causes psychosocial problems. A two-stage surgical approach consisting of maxillary distraction and mandibular setback was developed to overcome these problems. In this study, changes in maxillofacial morphology and velopharyngeal function were examined in 22 patients with cleft lip and palate who underwent this two-stage approach. Lateral cephalograms taken just before the first surgery, immediately after the second surgery, and at completion of the active post-surgical orthodontic treatment were used to examine maxillofacial morphology. Velopharyngeal function was evaluated by speech therapists using a 4-point scale for hypernasality. The average forward movement of the maxilla with surgery at point A was 7.5 mm, and the average mandibular setback at pogonion was 8.6 mm. The average relapse rate during post-surgical orthodontic treatment was 25.2% for the maxilla and 11.2% for the mandible. After treatment, all patients had positive overjet, and skeletal relapse was covered by tooth movement during postoperative orthodontics. Velopharyngeal function was not changed by surgery. This method can shorten the period during which the distractors have to be worn and reduce the patient burden.